THE FUTURE OF SCHOOL AND TECHNOLOGIES: SOME ASPECTS IN THE LIGHT OF THE DIALOGUE BETWEEN PAULO FREIRE AND SEYMOUR PAPERT - Castro, Rosane Michelli de [UNESP]; Catini Lanzi, Lucirene Andrea (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
We present in this article results of reflections on the school, aspects of its history and actuality, as well as its perspectives within the capitalist society, marked by socioeconomic inequalities, in the light of the dialogue between Brazilian and South African educators, Paulo Freire and Seymour Pappert, respectively, in the video entitled Seymour Papert and Paulo Freire: a conversation about computing, teaching and learning, about the future of the school and the role of technologies. These reflections originated from our activities developed in the course of Pedagogy of a public university of Sao Paulo, centrally in the discipline of Didactic I, whose concerns are fixed around two fundamental questions that are reflected on the formation and the work of the teacher, the Importance of conceptualizing and situating education and teaching not only in function of its aims, but also emphasizing its political function and its specificity and, attaching to this question, the necessity of the theoretical appropriations that underlie pedagogical and didactic theories, and From which derive the different methods and techniques of teaching, among which those developed through the technologies. As a result of our reflections, the political function and specificity of education and teaching, when recovered by the teacher, through educational foundations centered on the idea of education and teaching for all, and enhanced by the use of technology and its tools, strengthens The importance of the school that wants to be space and time for theoretical and social activities to be performed by the subjects in a constant process of development.
Keywords: Education; Technologies and their tools; Specificity and political function of education and teaching; Importance of school; Human development